Stimulation of Duodenal Biopsies and Whole Blood from Dogs with Food‐Responsive Chronic Enteropathy and Healthy Dogs with Toll‐Like Receptor Ligands and Probiotic Enterococcus faecium. (August 2014) - Schmitz, S.; Henrich, M.; Neiger, R.; Werling, D.; Allenspach, K.
Abstract The composition of the microbiome plays a significant role in the pathogenesis of inflammatory bowel disease (IBD) in humans and chronic enteropathies (CE) in dogs. The administration of probiotic micro‐organisms is one way of modulating the microbiome, but experiments elucidating mechanisms of action of probiotics in the intestine of healthy and CE dogs are lacking. The aim of our study was to investigate the effects of different Toll‐like receptor (TLR) ligands and Enterococcus faecium (EF) on ex vivo cultured duodenal samples and whole blood (WB) from dogs with food‐responsive chronic enteropathy (FRE) when compared to healthy dogs. Biopsy stimulation was performed in 17 FRE and 11 healthy dogs; WB stimulation was performed in 16 FRE and 16 healthy dogs. Expression of TLR2, 4, 5 and 9, IL‐17A, IL‐22, IFNy, TNFα, IL‐4, IL‐10, TGFβ and PPARy was determined in biopsies by quantitative polymerase chain reaction (PCR). In addition, production of TNFα, IL‐10, IFNy and IL‐17A protein in WB and biopsy supernatants was assessed by ELISA. Treatment with individual TLR ligands or EF induced a variety of changes in the expression of different TLRs and cytokines, but not necessarily a consistent change with a single stimulating agent. Even though cytokine protein could not be detected in supernatants from ex vivo stimulated biopsies, we found TNFα protein responses in blood to be opposite of the transcriptional responses seen in the biopsies. Stimulation of canine duodenal biopsies with TLR ligands can potentially induce anti‐inflammatory gene expression, especially in healthy tissue, whereas the effects of EF were limited.